The Qualities of The Teacher And Student In The Philosophical Views of Khoja Abdulkholik Gijduvani - Vohid qizi, Vohidova; qizi , Boltayeva (Buletin Antropologi Indonesia, 2025)
This article presents the wise advice of Khoja Abdulkholik Gijduvani on the qualities of the teacher and student, analyzing the correct structure of the teacher-student relationship. It discusses how the qualities of the teacher and the pivotal role of the teacher in shaping the student’s life are philosophically examined. By following the teacher’s instructions with patience and perseverance, a student can effectively utilize their time, turning into a valuable and knowledgeable person in society, as demonstrated by real-life examples. The article emphasizes that teachers entrusted with the physical and spiritual development of young generations must approach this immense responsibility with seriousness. Furthermore, the article highlights the importance of respecting the teacher-student relationship as an essential guiding principle for future generations, serving as an important school of thought for them to learn from.